Not engaged in education, employment or training (NEET) in an Arctic sociocultural context: the NAAHS cohort study - Bania, Elisabeth Valmyr; Eckhoff, Christian; Kvernmo, Siv (BMJ Open, 2019)
Source at https://doi.org/10.1136/bmjopen-2018-023705 . Objectives - The purpose of the study is to explore the prevalence and predictors of not engaged in education, employment or training (NEET) status in a multicultural young adult population in Northern Norway. Design and setting - The longitudinal design link a selfreported survey (2003–2005) with an objective registry linkage follow-up 8–10 years later. Participants - Of all 5877 tenth graders (aged 15–16 years) in Northern Norway, 83% of the total age cohort from all 87 municipalities participated in the baseline survey. The follow-up studies consisted of 3987 consent giving adolescents (68%), were 365 (9.2%) reported indigenous Sami ethnicity. Outcome measures - Youth NEET at the age of 23–25 years. Methods Explanatory - variables were sociodemographic factors (gender, ethnicity, residency, parental education), mental health problems and musculoskeletal pain in adolescence. Outcome variable characterised as NEETstatus was defined by no educational engagement, longterm recipient of sickness benefit, medical and nonmedical benefit receipt or long-term unemployment. Results - NEET-status in young adulthood was significantly higher among females (20.9%) than among males (16.2%). Ethnic differences occurred as being NEET among Sami males was significantly higher than among non-Sami males, 23.0% and 15.2% respectively. Minority Sami females experienced NEETstatus to a lower degree (16.6%) than non-Sami females (20.8%). Among females adolescent peer problems (adjusted OR=1.09) and hyperactivity problems (adjusted OR=1.10) were associated with later NEETstatus. Peer problems (adjusted OR=1.23), conduct problems (adjusted OR=1.17) and musculoskeletal problems (adjusted OR=1.15) in male adolescents were associated with later NEET-status, whereas emotional problems among males predicted significantly less later NEET- status (adjusted OR=0.88). We found lower parental education to be significantly associated with being NEET-later in young adults (females: adjusted ...